Implementasi Etika Bisnis Islam Pada Sistem Jual Beli: Studi Kasus Di Pasar Tradisional - Septiani, Septiani; Hadziq, M Fuad (Jurnal Ilmiah Ekonomi Islam, 2023)
In countries with a Muslim majority, such as Indonesia, people should use a transaction process that is accordance with sharia principle. However, in fact, there is a lot of fraud, injustice and violations in the buying and selling process in the market. This study analyzes the implementation of Islamic business ethics in the buying and selling system in traditional markets. This research was conducted on a sample of traditional market sellers and buyers. The case study sample is Pasar Minggu, Aji Jaya Village, KNPI Tulang Bawang, Lampung, Indonesia. This study uses a descriptive-qualitative method by collecting data through interviews with traders and buyers in traditional markets. This study produces an explanation which reveals that Islamic business ethics have been applied in the buying and selling process at the Sunday market, such as honesty, fairness, and cleanliness. However, there are still some violations of business ethics, such as fraud and price injustice. Further and measurable efforts are needed to increase the awareness of traders and buyers about Islamic business ethics and address violations for the legitimacy of the buying and selling process.